ANALISIS PENGARUH MODAL SENDIRI, MODAL PINJAMAN, VOLUME USAHA, DAN JUMLAH ANGGOTA TERHADAP SISA HASIL USAHA PADA KOPERASI SOPIR TRANSPORTASI SOLO - Fadjar Harimurti, Lisyani Agustina, Suharno & (Universitas Slamet Riyadi, 2016)
The purpose of this study was to determine the significance of the influence of their own capital, loan capital, the business volume and the number of members simultaneously on operating results in the Cooperative Transport driver Solo (Solo Kosti) Year 2005 - 2015. The research method using the case study method, the type of data used quantitative and qualitative data, the data source used secondary data. Data collection methods used documentation. Data analysis techniques used classical assumption test, multiple linear regression analysis, t-test, F and coefficient of determination. In conclusion: 1) There is a positive and significant influence on the rest of the equity in the operating results Transport Cooperative driver Solo (Solo Kosti). 2) There is no significant positive effect of loan capital, business volume, and the number of members to the rest of the results of operations in the Cooperative Transport driver Solo (Solo Kosti). 3) There is significant influence free variables own capital, loan capital, the business volume and the number of members simultaneously on the dependent variable is net income in the Cooperative Transport driver Solo (Solo Kosti).Keywords: equity, loan capital, business volume, number of members, net income